Passive leadership: relationships with trust and justice perceptions. Issue 1 (13th February 2017) - Holtz, Brian C.; Hu, Biyun
Abstract : Purpose: Despite its prevalence in organizations, passive leadership has received scant research attention compared to more active forms of leadership. The purpose of this paper is to demonstrate the significant impact that passive leadership can have on two core constructs in the organizational sciences – trust and perceptions of fairness. Design/methodology/approach: Data were collected through self-report questionnaires ( n =192), using a three-wave survey methodology in order to provide temporal separation between the predictor, mediator, and outcome variables. Findings: Passive leadership was negatively associated with cognition-based trust. Further, passive leadership exerted a negative indirect effect on employee perceptions of justice, through cognition-based trust. Research limitations/implications: Although this research was explicitly interested in employee perceptions, the use of self-report measures may be considered a study limitation. Practical implications: This study underscores that passive leadership may represent a serious impediment to effective supervisor-employee relations. Employees do not trust supervisors who display a passive leadership style and a lack of trust can lead employees to perceive the supervisor as unfair. Originality/value: This study contributes new insights into the psychological effects of passive leadership behavior by demonstrating the potential role of passive leadership in shaping employee perceptions of trust and fairness.